2007
DOI: 10.1074/jbc.c700052200
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Association of the Neuronal p35 Activator of Cdk5

Abstract: Cdk5 and its neuronal activator p35 play an important role in neuronal migration and proper development of the brain cortex. We show that p35 binds directly to ␣/␤-tubulin and microtubules. Microtubule polymers but not the ␣/␤-tubulin heterodimer block p35 interaction with Cdk5 and therefore inhibit Cdk5-p35 activity. p25, a neurotoxin-induced and truncated form of p35, does not have tubulin and microtubule binding activities, and Cdk5-p25 is inert to the inhibitory effect of microtubules. p35 displays strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 29 publications
2
49
1
Order By: Relevance
“…MTs in COS-7 cells disassembled and tubulin staining became diffuse in the cytoplasm when Cdk5/p35 was coexpressed with tNhtt-poly(Q)-EGFP, as occurred with nocodazole treatment. Although it was recently reported that p35 bound and stabilized MTs in vitro (Hou et al, 2007), MT stabilization was not observed in our cultured cells. Our results are consistent with previous reports demonstrating the requirement of MTs in cytoplasmic aggregate formation (Johnston et al, 1998;Iwata et al, 2005).…”
Section: Discussioncontrasting
confidence: 44%
“…MTs in COS-7 cells disassembled and tubulin staining became diffuse in the cytoplasm when Cdk5/p35 was coexpressed with tNhtt-poly(Q)-EGFP, as occurred with nocodazole treatment. Although it was recently reported that p35 bound and stabilized MTs in vitro (Hou et al, 2007), MT stabilization was not observed in our cultured cells. Our results are consistent with previous reports demonstrating the requirement of MTs in cytoplasmic aggregate formation (Johnston et al, 1998;Iwata et al, 2005).…”
Section: Discussioncontrasting
confidence: 44%
“…The p10 interaction in vivo with other cellular proteins, such as tubulin (microtubules) and calmodulin (31,74), may protect the activity of the Cdk5-p35 complex (and not the Cdk5-p25 complex) from p5 inhibition. In our experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of Tubulin Polymerization on Cdk5 Activity-Tubulin polymerization was performed as detailed in a previous report (31). Briefly, active kinase Cdk5-p35 (2 ng/l) or active Cdk5-p25 (1 ng/l) was incubated with ␤-tubulin (enzyme/tubulin at 1:100) in PEM buffer (80 mM PIPES, 2 mM MgCl 2 , 1 mM EGTA, pH 7.0) supplemented with 1 mM GTP at 35°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro MT assembly assay clearly demonstrated that C53/LZAP was associated with the assembled MT but did not bind MT directly (Figure 6 proteins. Such mediators may include p35 [26] and other potential C53/LZAP-interacting protein such as Disrupted-in-Schizophrenia 1 (DISC1) protein, which is also known to bind the microtubule [27,28]. Meanwhile, a relatively large fraction of cytoplasmic C53/LZAP is associated with light membranes, such as the ER (Figure 6B and [12]), probably through its interaction with the ER protein RCAD (also known as Ufl1, NLBP and MAXER) [12,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%